The mechanism for bond behavior of concrete with two-staged treated rubber filled steel tube - Abu Bakar, Nabilah; Safiee, Nor Azizi; Mohd Nasir, Noor Azline; Abdul Rahman, Muhammad Fakhrul Radzi; Midhin, Abdulrahman Khaleel (Taylor and Francis, 2022)
Rubberized concrete, due to its lower compressive strength, has been applied as the infill in concrete filled steel tube (CFST) to offset the strength reduction. A method to improve the rubberized concrete microstructure is through a two-staged rubber treatment, which incorporates the surface treatment of rubber and the use of blended cement. However, the bond behavior of such material in CFST has not been investigated. In this study, concrete filled steel tubes with different mixes and thicknesses were tested under push-out test to investigate the parameters influencing its bond behavior. The mixes include normal concrete, concrete with chemically treated rubber as 10% aggregate replacement, and concrete with two-stage rubber treatment incorporating 15% metakaolin as cement replacement. It is found that the wall thickness plays a major role in the bond strength of CSFT, and could be increased for square sections with very weak bond strength. Based on the experimental work, the improvement of microstructure due to the inclusion of metakaolin and surface treatment of rubber increases the bond strength significantly, even higher than the normal concrete. Thus, concrete with two-staged treated rubber CFST could be utilized as a construction member due to its comparable compressive and bond strengths.